In vivo osteogenic differentiation of stem cells inside compartmentalized capsules loaded with co-cultured endothelial cells - Correia, C. (2017)
Capsules coated with polyelectrolytes and co-encapsulating adipose stem (ASCs) and endothelial (ECs) cells with surface modified microparticles are developed. Microparticles and cells are freely dispersed in a liquified core, responsible to maximize the diffusion of essential molecules and allowing the geometrical freedom for the autonomous three-dimensional (3D) organization of cells. While the membrane wraps all the instructive cargo elements within a single structure, the microparticles provide a solid 3D substrate for the encapsulated cells. Our hypothesis is that inside this isolated biomimetic 3D environment, ECs would lead ASCs to differentiate into the osteogenic lineage to ultimately generate a mineralized tissue in vivo. For that, capsules encapsulating only ASCs (MONO capsules) or co-cultured with ECs (CO capsules) are subcutaneously implanted in nude mice up to 6 weeks. Capsules implanted immediately after production or after 21 days of in vitro osteogenic stimulation are tested. The most valuable outcome of the present study is the mineralized tissue in CO capsules without in vitro pre-differentiation, with similar levels compared to the pre-stimulated capsules in vitro. We believe that the proposed bioencapsulation strategy is a potent self-regulated system, which might find great applicability in bone tissue engineering. Statement of Significance The diffusion efficiency of essential molecules for cell survival is a main issue in cell encapsulation. Former studies reported the superior biological outcome of encapsulated cells within liquified systems. However, most cells used in TE are anchorage-dependent, requiring a solid substrate to perform main cellular processes. We hypothesized that liquified capsules encapsulating microparticles are a promising attempt. Inspired by the multiphenotypic cellular environment of bone, we combine the concept of liquified capsules with co-cultures of stem and endothelial cells. After implantation, results show that co-cultured capsules without in vitro stimulation were able to form a mineralized tissue in vivo. We believe that the present ready-to-use TE strategy requiring minimum in vitro manipulation will find great applicability in bone tissue engineering.